Sex Determination of in Vitro Produced Goat Embryos by Epididymal Spermatozoa Selected by Swim up Technique - Sura Shakir Hammood (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study was conducted to determine the sex of the male and female goat embryos produced in vitro fertilization by Epididymal spermatozoa of local buck and separated by swim-up technique. The sex of produced embryo was identified by polymerase chain reaction (PCR). Results indicate that the fertilization by Epididymal spermatozoa selected using Swim-up technique at 200×g centrifugation showed that 48.70 ±0.62 % of spermatozoa were detected in the supernatant while the precipitate contained 42.1±0.70. Spermatozoa in the supernatant were used for IVF of matured oocytes. The sex of goat embryos produced in vitro fertilization was determined by polymerase chain reaction (PCR) using specific primers to detect the SRY gene. The percentage of male embryos recorded 71.73% while female embryos recorded only 28.26% from the total goat embryos obtained after IVF by sperms selected using swim-up at centrifugation force of 200×g. It was concluded that the use of swim-up technique up at centrifugation force of 200×g on Epididymal spermatozoa showed the ability of selection male embryos in caprine.